Studies on Lipids Content in the Healthy Full Grown Larval Haemolymph, Silkglands and Food Leaves of Antheraea proylei Jolly (Saturniidae: Lepidoptera) - B. Prasad, Ok. Monoroma*, M. Chinamen, M. Kumar and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The estimation of lipids content in the healthy full grown larval haemolymph, silkglands and food leaves of Antheraea proylei Jolly was determined by extraction with chloroform and methanol following a standard method. The lipids content in the larval haemolymph varies from 65.69 to 67.21 mg/ml with a mean value of 66.54 ± 0.151 and 0.1430 to 0.1436 mg/mg fresh weight with a mean value of 0.1433 ± 0.00006 in the silkglands. While the lipids content in the food leaves (Quercus serrata) ranges from 0.0232 to 0.0264 mg/mg dry weight with a mean value of 0.0249 ± 0.00038. The multiple correlation co-efficient of silkglands on haemolymph and food leaves was found to be R2 = 72.0% and significant at 5% level.